Microencapsulation of Osmanthus essential oil by interfacial polymerization: Optimization, characterization, release kinetics, and storage stability of essential oil from microcapsules - Liu, Yanhong; Liu, Mengyao; Zhao, Juan; Wang, Dezhen; Zhang, Lingling; Wang, Hui; Cao, Wanqi; Wang, Shuo (Journal of food science, 2021)
In this paper, the interface polymerization method was used to prepare Osmanthus essential oil microcapsules. The optimal preparation process of Osmanthus essential oil microcapsules was explored as follows: the dosage ratio of Osmanthus essential oil to N100 was 6:1, the reaction temperature was 70°C, and the reaction time was 2 h. The encapsulation efficiency of Osmanthus essential oil microcapsules could reach 80.31%. The particle size distribution, morphology, chemical structure, and thermal stability of the obtained microcapsules were characterized by laser particle size analyzer, scanning electron microscopy, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The release kinetics and storage stability experiments of the microcapsules were studied. The results showed that the average volume diameter of the microcapsules was 101.2 µm. The microcapsules were in the shape of full spheres, with a smooth surface, low viscosity, and high elasticity. Microencapsulation improved the thermal stability of Osmanthus essential oil and promoted the slow release of essential oil. The synthesized microcapsules showed good storage stability under refrigerated and dark conditions, which indicated that microcapsules had broad application prospects in food, medicine, and other fields. Practical Application In this study, we prepared a polyurea membrane to encapsulate Osmanthus essential oil microcapsules by interfacial polymerization. The encapsulation conditions of the microcapsules were optimized and the structure of the microcapsules was characterized in this study. The results showed that microcapsules had a full spherical shape with a smooth surface, high elasticity, good sustained‐release ability, good thermal stability, and storage stability. These properties indicated that microcapsules have good application prospects and can be used as a high‐quality flavor with a long residual effect and high thermal stability for food and cosmetic scope.